Falciparum malaria-induced hypoglycaemia in a diabetic patient. - Shalev, O. (BMJ Group, 1992)
We report a patient with diabetes mellitus who suffered severe falciparum malaria complicated by profound and persistent hypoglycaemia. The hypoglycaemia evolved before therapy with quinine was begun and resolved with eradication of the parasitaemia. The patient reverted to her baseline hyperglycaemia despite continuation of quinine. This case illustrates the critical role of falciparum malaria in the pathogenesis of malaria-associated hypoglycaemia, rather than quinine-mediated mechanisms. Anticipation of hypoglycaemia in falciparum malaria and its vigorous treatment may improve the poor prognosis associated with this complication.